A new species of the genus Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from a lowland monsoon forest in Southern Vietnam - Yushchenko, Platon V.; Grismer, L. Lee; Bragin, Andrey M.; Dac, Le Xuan; Poyarkov, Nikolay A. (Zootaxa, 2023)
An integrative taxonomic analysis delimits and diagnoses the new species Hemiphyllodactylus cattien sp. nov. from Cat Tien National Park, Dong Nai Province, southern Vietnam—the eighth species of Hemiphyllodactylus to be described from Vietnam. The new species is recovered as the sister species to a clade comprised of H. indosobrinus from Laos and H. flaviventris from Thailand based on phylogenetic analyses using ND2 mtDNA gene sequences. Unlike the vast majority of Hemiphyllodactylus which are site-restricted upland endemics, Hemiphyllodactylus cattien sp. nov. is a lowland species collected from one of the most well-surveyed regions in Vietnam. Its discovery further emphasizes the need for continued re-sampling of survey sites already considered to be well-explored.